Chemistry for dummies - Moore, John T., 1947- (Hoboken, NJ : Wiley Pub., 2011)
A matter-of-fact guide to mastering the basics of chemistry.
The basic concepts of chemistry. What is chemistry, and why do I need to know some? ; Contemplating chemical calculations ; Matter and energy ; Something smaller than an atom? Atomic structure ; The periodic table (but no chairs) ; Balloons, tires, and scuba tanks : the wonderful world of gases -- A cornucopia of chemical concepts. Chemical cooking : chemical reactions ; The mole : can you dig it? ; Mixing matter up : solutions ; Thermochemistry : hot stuff ; Sour and bitter : acids and bases -- Blessed be the bonds that tie. Where did i put that electron? Quantum theory ; Opposites do attract : ionic bonding ; Sharing nicely : covalent bonding ; What do molecules really look like? Molecular geometry and hybridization ; Tackling periodic trends ; Examining the link between intermolecular forces and condensed states -- Environmental chemistry : benefits and problems. Cough! cough! hack! hack! Air pollution ; Examining the ins and outs of water pollution ; Nuclear chemistry : it'll blow your mind -- The part of tens. Ten serendipitous discoveries in chemistry ; Ten (or so) great chemistry nerds ; Ten terrific tips for passing Chem I ; The top ten industrial chemicals.
Includes index.
Keywords: Chemistry; Chemistry